2014
DOI: 10.1177/0022022114537704
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Versus Analytic Expressions in Artworks

Abstract: Previous research has documented systematic cultural variations in adults’ cognitive processes. In particular, research on culture and aesthetics suggests that East Asian adults’ aesthetic expression tends to be holistic and context-oriented, whereas North American adults’ aesthetic expression tends to be analytic and object-oriented (Masuda, Gonzalez, Kwan, & Nisbett, 2008). However, research focusing specifically on the developmental processes of such cultural differences in children’s artworks is lacking, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 42 publications
(78 reference statements)
1
33
1
Order By: Relevance
“…Research on culture and aesthetics in a developmental context has also demonstrated that aesthetic expressions are systematically different across cultures (Rübeling et al, 2011; Gernhardt et al, 2013; Ishii et al, 2014). In line with these findings, Senzaki et al (2014b) examined cultural variations in landscape artworks produced by primary school children in Japan and Canada, and demonstrated that once children understood the concept of a horizon (age 8 for both cultures), Japanese children drew the horizon higher in both studies and integrated more objects in their collages than did Canadian, the pattern of which is consistent with that of young adult data (Masuda et al, 2008c). …”
Section: The Dynamic Nature Of Culturementioning
confidence: 66%
See 4 more Smart Citations
“…Research on culture and aesthetics in a developmental context has also demonstrated that aesthetic expressions are systematically different across cultures (Rübeling et al, 2011; Gernhardt et al, 2013; Ishii et al, 2014). In line with these findings, Senzaki et al (2014b) examined cultural variations in landscape artworks produced by primary school children in Japan and Canada, and demonstrated that once children understood the concept of a horizon (age 8 for both cultures), Japanese children drew the horizon higher in both studies and integrated more objects in their collages than did Canadian, the pattern of which is consistent with that of young adult data (Masuda et al, 2008c). …”
Section: The Dynamic Nature Of Culturementioning
confidence: 66%
“…Their studies have demonstrated that East Asian cultural products such as landscape drawings (Masuda et al, 2008c; Senzaki et al, 2014b), the amount of information in conference posters and websites (Wang et al, 2012), and the physical environment of cities and towns (Miyamoto et al, 2006) contain more information that represents interdependence and a holistic way of understanding the world, whereas Western cultural products contain information that represents independence and an analytic way of understanding the world.…”
Section: The Cyclical Nature Of Culture and Psychementioning
confidence: 99%
See 3 more Smart Citations